2001
DOI: 10.1038/sj.bmt.1703102
|View full text |Cite
|
Sign up to set email alerts
|

Changes in autoimmune thyroid disease following allogeneic bone marrow transplantation

Abstract: Summary:Autoimmune diseases can be transmitted and eliminated by bone marrow transplantation (BMT). There have been several cases of autoimmune thyroid disease (AITD) occurring after BMT, but AITD remission has been rarely reported. We present four cases in which the remission or transfer of AITD occurred after an allogeneic BMT. Two patients with severe aplastic anemia (SAA) showed evidence of remission of Hashimoto's thyroiditis which they had before allogeneic BMT. One patient with SAA, which developed duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 10 publications
1
17
0
Order By: Relevance
“…Post-HSCT AITD was first reported in 1987, 16 and a total 17 cases have since been reported (Table 3). [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] They included five cases of hypothyroidism and 12 cases of thyrotoxicosis. The male to female ratio in HSCT recipients was roughly equal (1.83:1), but similar to our experience, donors were markedly skewed to females (0.23:1).…”
Section: Discussionmentioning
confidence: 99%
“…Post-HSCT AITD was first reported in 1987, 16 and a total 17 cases have since been reported (Table 3). [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] They included five cases of hypothyroidism and 12 cases of thyrotoxicosis. The male to female ratio in HSCT recipients was roughly equal (1.83:1), but similar to our experience, donors were markedly skewed to females (0.23:1).…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22] The AID preceded the onset of aplastic anemia by 0.2-25 (median 3) years. Prior treatment for AID included gold salts, antirheumatic or thyroistatic drugs in at least 10 patients.…”
Section: Allogeneic Sctx For Aplastic Anemia and A Concomitant Autoimmentioning
confidence: 99%
“…18,19 Four other patients received additional antithymocyte globulin alone (ATG) 15 or anti-lymphocyte globulin (ALG) together with procarbazine. 22 Standard graft-versushost prophylaxis was given to all patients post transplant and consisted of methotrexate and cyclosporine, alone, or in combination.…”
Section: Allogeneic Sctx For Aplastic Anemia and A Concomitant Autoimmentioning
confidence: 99%
“…Donor antibody transfers, immune-mediated injury, conditioning treatment effects, post-transplant medications and patient susceptibility may play a role in post-hematopoietic stem cell transplantation hypothyroidism. Case studies have shown that a donor with autoimmune thyroid disorder may transfer cell capable of injuring the recipient's thyroid gland after hematopoietic stem cell transplantation (Lee et al 2001;Marazuela, and Steegman 2000). Immune-mediated thyroid injury arising in the host has been suggested in other studies and may be a form of graftversus-host-disease (Kami et al 2001;Katsanis et al 1990;Somali et al 2005).…”
Section: Allogeneic Hematopoietic Stem Cell Transplantationmentioning
confidence: 99%